2013
DOI: 10.1271/bbb.130034
|View full text |Cite
|
Sign up to set email alerts
|

Salak Plum Peel Extract as a Safe and Efficient Antioxidant Appraisal for Cosmetics

Abstract: The antioxidant activities of Salak plum (Salacca edulis) peel extracts were assessed by 1, 1-diphenyl-2-picrylhydrazyl (DPPH), 2,2 0 -azino-bis(3-ethylbenzothaiazoline)-6-sulfonic acid (ABTS), and ferric reducing ability of plasma (FRAP) assays. The ethyl acetate (EtOAc) fraction was the most potent (DPPH IC50 ¼ 2:932 AE 0:030 g/mL, ABTS IC50 ¼ 7:933 AE 0:049 g/mL, FRAP EC ¼ 7;844:44 AE 40:734). Chlorogenic acid was detected as the marker (1:400 AE 0:102 g/kg). The EtOAc fraction was non-cytotoxic in vero and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(69 reference statements)
3
12
0
Order By: Relevance
“…Consistent with the DPPH platform, the ABTS test gave similar results, with EtOAcE being the most potent (IC 50 25.81 μg mL −1 ), which was significantly different from the other three extracts including EE (IC 50 131.88 μg mL −1 ), PEE (IC 50 115.74 μg mL −1 ), and WE (IC 50 115.86 μg mL −1 ). In line with the present result, the ethyl acetate extract of salak plum peel exhibited an excellent antiradical effect against ABTS radicals (IC 50 7.93 μg mL −1 ), which was much higher than its 70% ethanol extract (IC 50 22.48 μg mL −1 ) . The FRAP platform was employed to test the reduction potential of these four extracts toward Fe 3+ .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the DPPH platform, the ABTS test gave similar results, with EtOAcE being the most potent (IC 50 25.81 μg mL −1 ), which was significantly different from the other three extracts including EE (IC 50 131.88 μg mL −1 ), PEE (IC 50 115.74 μg mL −1 ), and WE (IC 50 115.86 μg mL −1 ). In line with the present result, the ethyl acetate extract of salak plum peel exhibited an excellent antiradical effect against ABTS radicals (IC 50 7.93 μg mL −1 ), which was much higher than its 70% ethanol extract (IC 50 22.48 μg mL −1 ) . The FRAP platform was employed to test the reduction potential of these four extracts toward Fe 3+ .…”
Section: Resultssupporting
confidence: 83%
“…In line with the present result, the ethyl acetate extract of salak plum peel exhibited an excellent antiradical effect against ABTS radicals (IC 50 7.93 μg mL −1 ), which was much higher than its 70% ethanol extract (IC 50 22.48 μg mL −1 ). 31 The FRAP platform was employed to test the reduction potential of these four extracts toward Fe 3+ . Interestingly, corresponding to its excellent potency against both DPPH and ABTS radicals, EtOAcE also displayed a significantly higher ability for reducing Fe 3+ , with the vitamin C equivalent antioxidant capacity (VCEAC) value being 81.16 VCEAC mg g −1 DW (milligram vitamin C equivalent per gram dry weight of the sample), demonstrating the most potent antioxidant capacity when compared with other three extracts, which were in the following order: PEE (15.36 VCEAC mg g −1 DW) > EE (8.92 VCEAC mg g −1 DW) > WE (5.23 VCEAC mg g −1 DW).…”
Section: Antioxidant Testmentioning
confidence: 99%
“…Luteolin caused toxicity from100 g/mL by altering organelles function in Vero cells and cytoplasmic membrane in lymphocytes. Others studies have also demonstrated lack of cytotoxic effect of chlorogenic acid and toxicity of luteolin on lymphocytes, Vero cells and kidney cells (Fujimoto et al, 2009;López-Posadas et al, 2008;Kang et al, 2011;Kanlayavattanakul et al, 2013). Caffeic acid was the more toxic compound.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, 2-furan carboxaldehyde, 4h pyran, phenyl ethyl alcohol, 1,2 furyl hydroxyl, 5formyl 2 furan, and benzene are important compounds in white arillus tissue. Ethylic acid phenyl alcohol, 2-methoxy vinyl, 2,4 xylene, 3,4 xylene, N-octyl alcohol, butyric acid, butanoic acid, 2-furan carboxaldehyde, 4h pyran, phenyl ethyl alcohol, 1,2 furyl hydroxyl, 5-formyl 2 furan, and benzene acts as an antioxidant (Kanlayavattanakul 2013;Zaini et al 2013), plays a role in metabolic processes (Ma et al 2014;Mancini et al 2015;Kochian et al 2015), and plant physiological processes (Ohki 1986;Harwood 1989;Wong and Tie 1993;Harwood 1996;Tsutsui et al 2011;Goulet et al 2012;Li et al 2013;Tyagi and Agarwal 2017). The study of molecular docking is important to determine the potential compounds of S. sumatrana.…”
Section: Discussionmentioning
confidence: 99%